Interdisciplinary Collaboration to Prevent and Reduce the Rate of Stunting in Toddlers in Tourism Areas - Khoirunnisa, Khoirunnisa; Kurniawan, Kurniawan; Akbarsyah, Nora (Universitas Padjadjaran, 2024)
Stunting is still a national problem in Indonesia, especially Pangandaran Regency. It has not reached the national target of zero stunting in 2023. An interdisciplinary approach between parents and cadres in screening growth and development status can support the government's targets in handling stunting. The aim of this community service was to improve the knowledge and skills of cadres and parents with toddlers regarding the growth and development of toddlers to prevent and handle stunting. The stages of the activity consisted of Training of Trainee, screening for the growth and development of toddlers, and Growth and Development Detection Training for Cadres. The participants of this activity were toddlers and Posyandu cadres in Bojong village, Pangandaran Regency. Growth and development screening was integrated with Posyandu activities using developmental pre-screening questionnaire (KPSP). Training for cadres used lecture method with modules as learning media. The results of the activity obtained the growth and development status of toddlers was not in accordance with age. Cadre knowledge has increased by 22% after participating in training activities. Training activities for cadres have a significant impact in improving the knowledge and skills of cadres related to the growth and development of toddlers as an effort to detect stunting early. The establishment of an information center for the community is expected to optimize stunting prevention efforts in the future. Keywords: cadre; development; growth; stunting; toddlers.